The Rosetta science operations and planning implementation. (November 2018) - Pérez-Ayúcar, Miguel; Ashman, Mike; Almeida, Miguel; Sitjà, Marc Costa; García Beteta, Juan José; Hoofs, Raymond; Kueppers, Michael; Yaseli, Julia Marín; Merritt, Donald; Nespoli, Federico; Suarez, Eduardo Sánchez
Abstract: The international Rosetta mission was launched on 2nd March 2004 for a ten year journey to its target destination, comet 67P/Churyumov-Gerasimenko. Following the January 2014 exit from a 31 month hibernation period, Rosetta approached and rendezvoused with the comet in August 2014. On 12th November 2014, the Philae lander was deployed from Rosetta onto the comet's surface after which the Orbiter continued its comet escort phase. The Rosetta Science Ground Segment supports the Project Scientist and the Science Working Team, in order to ensure the coordination, development, validation and delivery of the desired science operations plans and their associated operational products throughout the mission, and to ensure the preservation of adequate data to the Planetary Science Archive. Within the Science Ground Segment, the Operations and Planning Group is responsible for the medium, short and very short term cycles, a stepped sequential process that implements the higher level science long term plan into the final science pointing requests and the command sequences to be executed on board the spacecraft. In this paper we will present the Operations and Planning group and its science planning activities, focusing on the evolution of the Science Operations implementation through the Rosetta mission phases. We will describe the day-to-day work needed to achieve science operations around the challenging and previously unknown cometary environment, and the software tools that support the planning process. We will finally outline several conclusions after the experience gained in the ∼2 years of operations at the comet. Highlights: Space science operations discipline combines scientific and engineering knowledge. Rosetta successfully returned unique science results in its two years at comet 67P. Rosetta changed from a rigid long-lead concept to a close-to-execution agile planning. Rosetta integrated new planning rules in the harsh fickle comet environment. It is remarkable how fast planning was adapted while performing comet observations.